Does hip-muscle weakness is associated with impaired foot postures in volleyball players? - Özer, F. F.; Simsek, D.; Küçük, N.; Bidil, S. (Kinesiologia Slovenica, 2023)
This study aimed to explore the differences in the distributions of plantar pressure in dynamic states and assess the strength profiles in the hip muscle of professional volleyball players according to foot posture index. Dynamic plantar pressure distributions were evaluated via the Pedar®-X plantar pressure insole during walking. Load Cell sensors were used isometrically to measure hip adductor/abductor muscle strength. Independent-Samples t-Test was performed according to Levene\'s homogeneity test results. Pearson correlation coefficient was performed to understand the relationship between the variables. For these measurements, significance level was set as p<0.05. The right adductor and right abductor strength of the prone group had significantly lower than the neutral group (p <.05). Similarly, the left adductor strength of the prone group had significantly lower than the neutral group (p <.05). Also, plantar pressure distributions of volleyball players with prone feet were distributed evenly across metatarsal bones, but highly uniformly on the 1st, 2nd and 3rd metatarsal head and midfoot regions in dynamic walking. Results between the neutral and prone foot posture group found a moderate negative relationship (r = -.570; -,529) between both right and left adductor hip strength and foot posture. Finally, in right and left abductor hip strength to foot posture a low negative relationship was found (r = -.471; -375). Reduced strength of the hip abductor relative to the adductor is associated with increased pronation at the foot. Furthermore, the decrease in arch height increased the risk of lower extremity injuries related to excessive use, including patellofemoral pain syndrome and medial tibial stress syndrome, as well as may have a negative effect on jumping performance.